Influence of two pt(iv) complexes on viability, apoptosis and cell cycle of B16 mouse melanoma tumors - Kaznica, A.; Drewa, T.; Lakomska, I.; Ryta-Stamirowska, P.; Debski, R.; Styczynski, J.; Drewa, G.; Szłyk, E. (Experimental Oncology, 2009)
Several platinum(IV) complexes are showing considerable promise in initial trials, producing reactive intermediates that then interact with DNA.
Aim: To perform in vitro study of two new platinum(IV) complexes cytotoxic effect on B16 mouse melanoma cells. Methods: PtCl₄
(dbtp)₂ and
PtCl₂
(6mp)₂
complexes were prepared. PtCl₄
(dbtp)₂ was created as modification of PtCl₄
(dmtp) test previously.Apoptosis and necrosis were examined
using flow cytometry, upon Annexin V/PI staining. Results: LC₁₀,LC₅₀ andLC₉₀ parameters established for PtCl₄
(dbtp)₂
were as following:
2.6, 17.0, 58.0 μmol/L. However LC₁₀ andLC₅₀ established for PtCl₂
(6mp)₂
were 1.2 and 14.0μmol/l respectively. The both complexes induced
apoptosis. PtCl₂
(6mp)₂
induced cell cycle arrest in G0/G1, while PtCl₄
(dbtp)₂ — in S-phase. Conclusions: PtCl₄
(dbtp)₂
appeared to be more
cytotoxic against B16 cells than PtCl₂
(6mp)₂
. Apoptosis was the main mechanism of cell loss in cultures incubated with both tested complexes.